Immune checkpoint inhibitor combination therapies very frequently induce secondary adrenal insufficiency - Katsunori Manaka (Nature Portfolio, 2021)
Abstract Immune checkpoint inhibitors (ICIs) are potent therapeutic options for many types of advanced cancer. The expansion of ICIs use however has led to an increase in immune-related adverse events (irAEs). Secondary adrenal insufficiency (AI) can be life-threatening especially in patients with delayed diagnosis. We retrospectively investigated secondary AI in ICI-treated patients. A total of 373 cancer patients treated with ICIs were included and evaluated. An adrenocorticotropic hormone (ACTH) deficiency was described in 13 patients. Among 24 patients with a combination of nivolumab and ipilimumab therapy, 7 patients (29%) developed secondary AI in a median time of 8 weeks during the combination therapy and 2 of 15 patients (13%) developed isolated ACTH deficiency during maintenance nivolumab monotherapy following the combination therapy. More than half of the patients (4/7) with a combination therapy-induced multiple anterior hormone deficiencies was diagnosed as secondary AI based on regular ACTH and cortisol tests with slight subjective symptoms. Secondary AI can arise frequently and rapidly in cancer patients receiving a combination ICI therapy, and thus we speculate active surveillance of AI using regular ACTH and cortisol tests during the combination therapy might be useful for avoiding life-threatening conditions due to secondary AI.